1996
DOI: 10.1093/intqhc/8.2.153
|View full text |Cite
|
Sign up to set email alerts
|

Patients Not Included in Medical Audit Have a Worse Outcome Than Those Included

Abstract: The aim of the present investigation was to analyse a clinical database in order to see how many patients were not included in medical audit and to see whether the outcome of the non-registered patients differed from that of the registered patients. Two independent surgeons studied the records of all infrainguinal bypass operations performed at six vascular surgical departments over a three-year period. A total of 684 bypass operations was reported to the register, of which 636 could be reviewed. One-hundred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 6 publications
0
39
0
Order By: Relevance
“…107 It has also been suggested that missing cases tend not to be missing at random, with the worst outcome data often excluded. 177 For these reasons, registries are not able to answer all the pertinent questions relating to treatments but, in combination with well-conducted RCTs, are likely to provide the best evidence for making public health decisions.…”
Section: Registry Datamentioning
confidence: 99%
“…107 It has also been suggested that missing cases tend not to be missing at random, with the worst outcome data often excluded. 177 For these reasons, registries are not able to answer all the pertinent questions relating to treatments but, in combination with well-conducted RCTs, are likely to provide the best evidence for making public health decisions.…”
Section: Registry Datamentioning
confidence: 99%
“…The authors concluded that "Overall judgment of the performance of an individual department may be impaired by cases not included in the register." [ 4 ] The above example demonstrates the importance of verifying the completeness of data within a database. In addition to verifying the completeness of data within a database, it is imperative to verify the accuracy of the data.…”
Section: The Impact Of Missing or Inaccurate Datamentioning
confidence: 96%
“…Indeed, it is established that patients not included in a medical audit have higher rates of morbidity and mortality than those are included in the audit [ 4 ]:…”
Section: The Impact Of Missing or Inaccurate Datamentioning
confidence: 99%
“…this also makes adequate research impossible and might mislead authorities in healthcare, politicians, and policy makers in decisions as well as in giving invalid information to the public (3,4). the aim of this study was to present a validation process, pursued over time, with regard to completeness, overall correctness, and correctness of rare adverse events for GallRiks concerning cholecystectomies.…”
Section: Introductionmentioning
confidence: 99%